2019
DOI: 10.1101/814368
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Short-term circulating tumor cell dynamics in mouse xenograft models and implications for liquid biopsy

Abstract: Motivation: Circulating tumor cells (CTCs) are important in hematogenous cancer metastasis, and are usually studied by isolation from small peripheral blood samples. However, little is known about the shortterm dynamics of CTC in vivo. Methods:We recently developed an instrument called 'diffuse in vivo flow cytometry' (DiFC), that allows counting of fluorescently-labeled circulating cells without drawing blood samples. DiFC samples 50L of circulating peripheral blood per minute, allowing continuous, non-invas… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 44 publications
3
14
0
Order By: Relevance
“…We also sincerely thank Dr. Miguel Martin (Universidad Complutense, Madrid, Spain) for kindly sharing data. This manuscript has been released as a pre-print at ( 51 ).…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…We also sincerely thank Dr. Miguel Martin (Universidad Complutense, Madrid, Spain) for kindly sharing data. This manuscript has been released as a pre-print at ( 51 ).…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…Previous studies have reported the underlying mechanisms of the kinetics of CTCs (binding/unbinding mechanism), adhesion processes, , their survival mechanisms in blood, and interactions with blood cells and endothelium, using diverse set of ligands and receptors . Various in vivo animal models , and in vitro models for CTC adhesion assays and their intravastion/extravasation have accordingly been explored previously. Despite these advancements, dynamic evolution of CTCs in a physiologically replicative vascular model is yet to be deciphered.…”
Section: Introductionmentioning
confidence: 99%
“…Although these are widely used in biomedical research, they are far from optimal for a number of reasons. In particular, small blood samples provide poor statistical sampling of the circulating blood volume [13][14][15], blood is known to degrade rapidly after removal from the body [16], and enrichment can cause cell loss or dissolution [17][18]. Moreover, in the case of small animal studies CTCs may be so rare that it is necessary to draw and analyze the entire blood volume, which requires euthanizing the animal [19].…”
Section: Introductionmentioning
confidence: 99%